Pengaruh Total Asset Turn Over (TATO) dan Debt to Asset Ratio (DAR) Terhadap Return on Assets (ROA) pada PT. Unilever Indonesia Tbk - Sucinang, Novita; Huda, Nurul; Mardian, Irma (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO) and Debt to Asset Ratio (DAR) on Return on Assets (ROA) at PT Unilever Indonesia Tbk during the 2015–2025 period. This research uses an associative quantitative approach with secondary data obtained from the company's annual financial statements. The sample consists of financial statement data for eleven years selected through purposive sampling. Data analysis was conducted using multiple linear regression analysis, including classical assumption tests, correlation coefficient analysis, coefficient of determination, t-test, and F-test with the assistance of SPSS software. The results indicate that Total Asset Turnover (TATO) has a positive and significant effect on Return on Assets (ROA), meaning that higher efficiency in asset utilization contributes to increased profitability. Meanwhile, Debt to Asset Ratio (DAR) has a negative and significant effect on ROA, indicating that a higher proportion of debt financing tends to reduce profitability due to increased financial burdens. Simultaneously, TATO and DAR significantly influence ROA. The coefficient of determination shows that both variables explain 66.1% of the variation in ROA, while the remaining 33.9% is influenced by other factors outside the research model. These findings suggest that effective asset management and prudent debt control are important factors in improving company profitability